Investigation of the diagnostic accuracy of basophil activation test for allergic phenotypes of rhinitis - Testera Montes, Almudena; Ariza Veguillas, Adriana; Sola-Martínez, Rosa Alba; Aranda, Carlos José; Bentabol-Ramos, Guillermo; Sánchez-Torralvo, Dulce; Mayorga Mayorga, Cristobalina; Torres-Jaén, María José; Eguiluz-Gracia, Ibón; Rondón Segovia, Carmen (Wiley, 2024)
Introduction: Basophil activation test (BAT) might be an alternative to nasal allergenchallenge (NAC) to identify the allergic etiology in rhinitis patients. Here, we investi-gate the diagnostic performance of BAT for allergic phenotypes of rhinitis.Methods: Rhinitis patients and healthy controls were subjected to NAC withDermatophagoides pteronyssinus (DP), Alternaria alternata (AA), grass (GP) and olive(OP) pollens. Rhinitis subjects also underwent skin prick test (SPT) with relevant al-lergens. Patients were classified into allergic rhinitis (AR, positive NAC and SPT), localallergic rhinitis (LAR, positive NAC and negative SPT), dual allergic rhinitis (DAR, de-fined as AR for ≥1 allergen and LAR for ≥1 allergen), and non-allergic rhinitis (NAR,negative NAC and SPT) phenotypes. BAT with DP, AA, GP and OP was conducted instudy individuals and compared with NAC results.Results: A total of 47 AR, 31 DAR, 26 LAR, 12 NAR and 21 control subjects were re-cruited. The best positivity cut-offs of BAT for DP-, AA-, GP- and OP-driven allergy (allphenotypes) were a %CD63 cells of 8.650, 14.250, 26.200, and 12.780, respectively(AUC 0.851, 0.701, 0.887, and 0.921, respectively).Sensitivity, specificity, negative and positive predictive values of BAT (all pheno-types) ranged 43.5%(AA)-83.3%(OP), 88.9%(GP)-100%(AA), 87%(GP)-100%(AA), and61.1%(DP)-80.0%(pollens), respectively. BAT identified 79%–100% of SPT-positive aller-gies (AR and DAR), and 25%–75% of SPT-negative allergies (LAR and DAR), while ≤10%of NAR/HC subjects tested positive. BAT positivity correlated with rhinitis severity inLAR patients (p = 0.018), and associated with conjunctivitis (p = 0.015) in allergic subjects.
Keywords: Basófilos; Alergia; Allergic rhinitis; Basophil activation test; Dual allergic rhinitis; Local allergic rhinitis; Nasalallergen challenge